Analisis Pengaruh Persepsi Mahasiswa Akuntansi Terhadap Profesi Akuntan di Kota Batam - Ria Karina; Milenia Panca Wijaya (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2021)
This study aims to determine the effect of accountant’s negative attitudes, image of profession, job outcomes and job demands on accounting profession in Batam City. The sampling method uses the Slovin formula. Total respondents were 330 students from 5 universities in Batam City. The data collection method used is questionnaires survey. The result of the questionnaires validity test on 26 questions stated valid. The data used in this study were tested using SPSS version 24. Based on the results of hypothesis testing, it can be concluded that all independent variables are significant. Perception of accountant’s negative attitudes have a significant negative effect on accounting profession. Meanwhile, the image of profession, job outcomes and job demands have a significant positive effect on accounting profession.